Prenatal ultrasound diagnosis and prognosis of fetus with isolated filar cyst: a retrospective analysis - Chen, Song; Tu, Peng; Mu, Lan (Frontiers in Medicine, 2024)
Objective This study aimed to investigate the prenatal ultrasonographic diagnosis and prognosis of fetuses with isolated filar cysts (FCs). Methods The ultrasonographic features, reasons for missed diagnosis, and prognosis of eight isolated FCs diagnosed using ultrasound were analyzed retrospectively through follow-up. Results Eight isolated FCs showed round or fusiform cystic anechoic areas at the end of the conus medullaris. Among them, six cases were prenatally diagnosed and the other two cases were diagnosed after birth. Of the six cases diagnosed prenatally, four (66.7 %) disappeared during pregnancy, and the shortest time to disappearance was one month after the first diagnosis. All patients were followed up without any clinical symptoms or functional abnormalities. Conclusion Isolated FCs may exhibit physiological variations that disappear spontaneously during pregnancy and usually have no clinical symptoms. They are usually benign and have a good prognosis. Ultrasonography is helpful for the diagnosis and follow-up of FCs.